A study of the new generation of the advance system tongue implants: three- and six-month effects of tongue to mandible tethering for obstructive sleep apnea - Pavelec, Vaclav; Hamans, Evert; Stuck, Boris (The laryngoscope, 2011)
OBJECTIVES/HYPOTHESIS: Treatment of hypopharyngeal collapse of upper airway is a surgical challenge in obstructive sleep apnea (OSA) patients who fail continuous positive airway pressure (CPAP). - STUDY DESIGN: A prospective, nonrandomized, multicentered, feasibility study. - METHODS: Nineteen OSA patients with an apnea-hypopnea index (AHI) between 15 and 50 with CPAP intolerance were included in the study. Baseline polysomnography (PSG) was measured, and 3- and 6-month postoperative PSGs were recorded. Preoperative and postoperative home sleep studies, cephalographs, and videoendoscopy were performed. Additionally, the subjects completed the Epworth Sleepiness Scale (ESS), Patient and Bed Partner Snoring Questionnaire, Functional Outcomes of Sleep Questionnaire, and Throat Questionnaire. - RESULTS: AHI dropped from 33.8 at baseline to 18.6 at 3-month follow-up and to 24.3 at 6-month follow-up, respectively. Overall surgical success was 38.9% as defined by a 50% drop in AHI to a score below 20 at 6 months. ESS decreased from 11.4 to 6.1 and 7.4 at 3 months and 6 months, respectively. Snoring intensity was reduced from 7% to 3.8% at 3 and 6 months, respectively. Quality of life was improved from 15.6 to 17.9 (14.3%) and 18.1 (15.6%) at 3 months and 6 months, respectively. - CONCLUSIONS: The rates of surgical success, feasibility, and safety were satisfactory. Further technical device improvement is necessary and must be based on a new understanding of tongue forces.
Gesehen am 05.10.2022